Mirror Therapy Using Gesture Recognition for Upper Limb Function, Neck Discomfort, and Quality of Life After Chronic Stroke: A Single-Blind Randomized Controlled Trial - Choi, Ho-Suk (Med Sci Monit, 2019)
BACKGROUND: Mirror therapy for stroke patients was reported to be effective in improving upper-extremity motor function and daily life activity performance. In addition, game-based virtual reality can be realized using a gesture recognition (GR) device, and various tasks can be presented. Therefore, this study investigated changes in upper-extremity motor function, quality of life, and neck discomfort when using a GR device for mirror therapy to observe the upper extremities reflected in the mirror. MATERIAL/METHODS: A total of 36 subjects with chronic stroke were randomly divided into 3 groups: GR mirror therapy (n=12), conventional mirror therapy (n=12), and control (n=12) groups. The GR therapy group performed 3D motion input device-based mirror therapy, the conventional mirror therapy group underwent general mirror therapy, and the control group underwent sham therapy. Each group underwent 15 (30 min/d) intervention sessions (3 d/wk for 5 weeks). All subjects were assessed by manual function test, neck discomfort score, and Short-Form 8 in pre- and post-test. RESULTS: Upper-extremity function, depression, and quality of life in the GR mirror therapy group were significantly better than in the control group. The changes of neck discomfort in the conventional mirror therapy and control groups were significantly greater than in the GR mirror therapy group. CONCLUSIONS: We found that GR device-based mirror therapy is an intervention that improves upper-extremity function, neck discomfort, and quality of life in patients with chronic stroke.